CENTRAL COMPOSITE DESIGN TO DEVELOP A ROBUST REVERSED-PHASE THIN-LAYER CHROMATOGRAPHY/DENSITOMETRY METHOD FOR QUANTIFICATION OF PARABENS IN COSMETIC PREPARATIONS - Jayaseelan, Kavitha; Lakshmi, Karunanidhi Santhana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The current study was framed with a view to develop a simple, sensitive and a rapid reversed-phase thin-layer chromatography (RP-TLC)/ densitometry method for quantification of parabens (methyl, ethyl, propyl, and butyl) in various cosmetic preparations available in local market. Moreover, robustness testing was planned to be performed applying a central composite design (CCD). Methods: The desired chromatographic separation was achieved on RP-TLC/densitometry plates precoated with Silica gel 60 GF254 on aluminum sheet, employing methanol:toluene:acetonitrile:glacial acetic acid as mobile phase in the ratio of 3:5:1.8:0.2 v/v/v/v and detection was carried out at 256 nm. Results: The mobile phase used gave an excellent resolution of all the four separated parabens. The method was found linear over a wide range of 6.25- 400 ng/spot. The optimized method was validated by measuring various validation parameters. CCD was employed to check the robustness of the method at three-factor levels. The developed and optimized method was used to quantify parabens in 30 different cosmetic products procured from local market. Conclusion: The proposed and developed RP-TLC/densitometry method can be applied for routine analysis of all the parabens in cosmetic products and can also be extended to the analysis in pharmaceuticals and food products.